2018
DOI: 10.3390/ijms19061701
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Physical Rehabilitation with Adjuvant Testosterone to Promote Neuromuscular Recovery after Spinal Cord Injury

Abstract: Neuromuscular impairment and reduced musculoskeletal integrity are hallmarks of spinal cord injury (SCI) that hinder locomotor recovery. These impairments are precipitated by the neurological insult and resulting disuse, which has stimulated interest in activity-based physical rehabilitation therapies (ABTs) that promote neuromuscular plasticity after SCI. However, ABT efficacy declines as SCI severity increases. Additionally, many men with SCI exhibit low testosterone, which may exacerbate neuromusculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 296 publications
(433 reference statements)
0
37
0
Order By: Relevance
“…Bone loss, muscle loss, and impaired muscle contractile properties are hallmarks of SCI (Biering‐Sorensen et al, ) that contribute to the high fracture risk in this population (Cirnigliaro et al, ). Reduced weight bearing and low testosterone (Abilmona et al, ) are factors that influence these bone and muscle deficits, suggesting that combinatory therapies addressing both impairments may enhance musculoskeletal recovery after motor‐incomplete SCI (Otzel, Lee, et al, ). To address this possibility, we conducted two preliminary studies to examine the acute effects of a standardized quadrupedal bodyweight‐supported TM training regimen (two 20‐min bouts/day, 5 days/week) on recovery of cancellous bone microstructural variables and muscle mass in skeletally mature rodents after severe SCI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bone loss, muscle loss, and impaired muscle contractile properties are hallmarks of SCI (Biering‐Sorensen et al, ) that contribute to the high fracture risk in this population (Cirnigliaro et al, ). Reduced weight bearing and low testosterone (Abilmona et al, ) are factors that influence these bone and muscle deficits, suggesting that combinatory therapies addressing both impairments may enhance musculoskeletal recovery after motor‐incomplete SCI (Otzel, Lee, et al, ). To address this possibility, we conducted two preliminary studies to examine the acute effects of a standardized quadrupedal bodyweight‐supported TM training regimen (two 20‐min bouts/day, 5 days/week) on recovery of cancellous bone microstructural variables and muscle mass in skeletally mature rodents after severe SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Lin et al reported that young female rodents exhibited a degree of spontaneous locomotor improvement after severe SCI that was comparable to that observed in our male SCI+TE+TM animals. As discussed above, intersex comparison of functional recovery after SCI is confounded by the potential neuroprotective effects of higher estradiol in females (Otzel, Lee, et al, ). We observed no differences in circulating estradiol among groups in our main study and no associations among estradiol and BBB scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The secondary parenchymal damage is of prolonged nature, based on which candidate treatment modalities have been developed [13][14][15][16]. The severity of the initial TSCI may serve as an indicator of the characteristics and degree of the secondary response; it may also be used to determine optimal treatment modalities [17,18].…”
Section: Introductionmentioning
confidence: 99%